Предмет: Алгебра,
автор: Mimimimimi666
1. Найдите f (3 - √2) + f (2 + √2), если f (х) = х^2 - 7
Ответы
Автор ответа:
0
Найдите f (3 - √2) + f (2 + √2), если f (х) = х^2 - 7
(3 - √2)^2 - 7 + (2 + √2)^2-7 = 9-6V2+2-7+4+4V2+2-7=
=3-2V2
(3 - √2)^2 - 7 + (2 + √2)^2-7 = 9-6V2+2-7+4+4V2+2-7=
=3-2V2
Похожие вопросы
Предмет: Английский язык,
автор: oksankalive
Предмет: Українська література,
автор: pcelobavyrod2
Предмет: Литература,
автор: tabynbaevr
Предмет: Математика,
автор: stepanenkdmi
Предмет: Литература,
автор: Касенбаева